Оntology based systemazing of the science information devoted to waste utilizing by methanogenesys - Shapovalov, Yevheniy B.; Shapovalov, Viktor B.; Stryzhak, Oleksandr Ye.; Salyuk, Anatoliy I. (ІТГІП, 2018)
Quantity of the scientific materials in the field of biogas production is growing. Thus, it is actual to provide informational management of it. Previously text documents and not-interactive pictures were used to describe it. The approach to systematization of scientific information on the production of biogas based on the ontological IT platform of TODOS is developed. It is proposed to separate the semantic characteristics of each work for their further introduction it into the IT platform of the TODOS. To construct a system of ranking of previous studies, we have identified the semantic characteristics of scientific research devoted to the production of biogas from chicken manure. Temperature (°C), volume of reactor (l), chicken manure content (%), moisture content (%), active sludge content (%), final solids content (%), biogas production and methane (ml/g TS), methane content (%), year of the research, ammonium nitrogen content (mg/l), VFA (mg/l), pH is final, initial pH, minimum pH, maximum pH were used to create ontology management system of the previous researches devoted to biogas production. The characteristics of the microorganisms were used to create the ontology based system of the microorganism selection. Google sheets was used to create base of knowledge and previous researches. An ontological graph with a ranking function for previous scientific research and a system of selection of microorganisms has been developed. Thus, the proposed systems allow to systematize previous research and theoretical information devoted to help of ontological graphs and provide information management in this field. Developed approaches allow us to analyze the results of previous research and theoretical information which provides systemizing of information and information management in general.
Використання онтологічних інструментів для систематизації та аналізу інформації щодо утилізації відходів шляхом метаногенезу
Keywords: biogas information; ontology; information management; TODOS; systematization; 573.6.086